Between Revelation and Revolution: H.O.S. Tjokroaminoto’s Quranic Hermeneutics and the Formation of Islamic Socialism - Rosalnia, Rika Leli Dewi Khusaila (Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
This article examines the ontological and epistemological foundations of H.O.S. Tjokroaminoto’s interpretation of sacred texts, as well as his hermeneutical commitment to the Quran as a project of knowledge and structural decolonization. As a prominent figure in the Indonesian Islamic political movement in the early twentieth century, Tjokro synthesized nationalism, socialism, and religiosity into an anti-colonial framework of thought. Living under the shadow of Western colonialism and capitalism, he sought to construct an antithesis to colonial hegemony through the Sarekat Islam (SI) movement and intellectual discourse based on Quranic values. Employing qualitative research with a hermeneutical approach to a range of Tjokroaminoto’s intellectual artifacts, this study finds that Tjokroaminoto interpreted the Quran from two interrelated perspectives: theologically, as a form of obedience and submission to divine revelation, and sociologically, as a moral and political imperative to free humans from oppression. His interpretation reflects a praxis-oriented epistemology rooted in the basic values of Islamic socialism, namely unity of the people, with four hermeneutic keys structured around four hermeneutical principles: equality, brotherhood, independence, and the cultivation of democratic ideals. Tjokroaminoto’s hermeneutics presents a reading that transcends dogmatic and textual boundaries, transforming the Quran into both a theological foundation and a political manifesto for liberation. Through this perspective, the Quran emerges as a living and dynamic text that inspires social change and national awakening.